Fiber-toughened aluminum-based porous composite material and preparation method thereof
Patent Information
- Application Number
- CN202411676982.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
The existing aluminum-based porous composite materials have high brittleness, resulting in low toughness and tensile strength, and the agglomeration problem of fibers in the matrix leads to uneven distribution of fibers and insufficient interface bonding, which affects the performance of the material.
The fiber/aluminum-based porous composite material was prepared by vacuum seepage method. By first preparing a uniformly dispersed preform of fibers and hollow spheres, carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA) were used as dispersants and adhesives to avoid fiber agglomeration, and aluminum seepage and solidification were carried out at high temperature.
It significantly improves the toughness and tensile strength of the material, ensures uniform distribution of fibers, and sufficient interface combination, improves the overall performance of the material, while maintaining low density characteristics.
Smart Images

Figure HDA0005147275650000011 
Figure HDA0005147275650000012
Abstract
Description
Technical field:
[0001] The invention belongs to the technical field of metal-based porous composite materials, and in particular relates to a method for preparing an aluminum-based porous composite material containing fibers. Background technology:
[0002] In recent years, the research on hybrid composites of multiple reinforcement materials has received increasing attention because these composites have great potential for customized applications. Ceramic hollow sphere / aluminum-based porous composites are a new type of composite material composed of ceramic hollow spheres and aluminum alloys. They have the characteristics of low density, high specific strength, high specific stiffness, good energy absorption capacity, good damping performance, and strong material design. However, since ceramic hollow spheres are brittle materials and account for a large proportion of aluminum-based porous composites, they have the disadvantages of low toughness and low tensile strength. Fibers are added to aluminum-based porous composites to make fiber / aluminum-based porous composites. The addition of fibers can solve the disadvantage of large brittleness of ceramic hollow sphere / aluminum-based porous composites. Fiber / aluminum-based porous composites have excellent room temperature and high temperature mechanical properties, and have higher strength, stiffness, heat resistance and fracture toughness than aluminum-based porous composites. Fiber / aluminum-based porous composites integrate many excellent properties of fiber toughening, ceramic reinforcement and foam metal materials, making them have broad application and research prospects in many fields, such as aerospace, military defense and transportation construction.
[0003] Although adding fibers can improve the brittleness of materials, the difficulty in preparing fiber / aluminum-based porous composite materials lies in the problem of fiber agglomeration in the matrix. Fiber agglomeration leads to uneven fiber distribution and insufficient interface bonding between the fibers and the Al matrix, which is not conducive to improving the performance of aluminum-based porous composite materials. In aluminum-based composite materials, ball milling is usually used to disperse the fibers in the material, but since the hollow spheres in the porous composite materials will be broken during the ball milling process, the ball milling dispersion method is not suitable. It is difficult to disperse short fibers in aluminum-based porous composite materials. Therefore, the development of domestic fiber / aluminum-based porous composite technology is relatively slow. Although relevant research has begun, a mature process has not yet been formed, and there is a lot of room for improvement. Summary of the invention:
[0004] In view of the problem of large brittleness of existing aluminum-based porous composite materials, the present invention provides an improved preparation process, first preparing a preform in which fibers and hollow spheres are evenly dispersed, and preparing the fiber / aluminum-based porous composite material by a vacuum infiltration method. The material significantly improves toughness without increasing density. The process can adjust the type, length and content of the fibers, as well as the type and size of the hollow spheres. In the dispersion process, carboxymethyl cellulose (CMC) plays a dispersing role, effectively avoiding agglomeration between fibers; polyvinyl alcohol (PVA) provides a bonding effect, so that the preform has a certain strength in the subsequent preparation process.
[0005] Its preparation method is as follows:
[0006] 1. Sol precursor configuration:
[0007] a. The process of preparing SiO2 sol is as follows:
[0008] Step 1, adding tetraethyl orthosilicate (TEOS) to a specified amount of ethanol and mixing thoroughly for use;
[0009] Step 2, measuring designated amounts of deionized water and ethanol, and dropping a certain amount of hydrochloric acid into the mixture, and mixing thoroughly;
[0010] Step 3: Under constant temperature stirring, slowly add the mixture of water and hydrochloric acid into the mixture of ethyl orthosilicate and ethanol according to the ratio, heat and stir under closed conditions to obtain the required SiO2 sol.
[0011] b. The process of preparing TiO2 sol is as follows:
[0012] Pour tetrabutyl titanate into anhydrous ethanol and stir to make the mixed solution uniform. While stirring, slowly drip acetic acid, then slowly add a certain amount of anhydrous ethanol and distilled water mixed solution and continue stirring for about 3 hours to form a transparent homogeneous TiO2 sol.
[0013] 2. Fiber pretreatment: Fiber pretreatment is divided into three processes: degumming, roughening and sol-gel. First, soak the fiber in acetone to remove the glue. Some types of fibers are then soaked in a certain concentration of NaOH solution to roughen the fiber surface. Then, they are rinsed with distilled water several times to remove the residual alkali solution and dried. Finally, some types of fibers are immersed in the sol, infiltrated under ultrasound for 5 minutes, and after sufficient drying, the temperature is raised to 450-500℃ at 5℃ / min for sintering to obtain a coating on the fiber surface.
[0014] 3. Preparation of fiber dispersant: Under the conditions of stirring with an electric stirrer and heating in a water bath, carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and an antistatic agent are slowly added into distilled water to prepare a fiber dispersant.
[0015] 4. Preparation of hollow ball slurry: Weigh the fly ash hollow balls with an electronic balance, add fiber dispersant, and fully mix under ultrasonic water bath heating and stirring conditions to form a suspension for use.
[0016] 5. Preparation of hollow fiber ball slurry: Weigh a certain amount of fiber with an electronic balance, add the fiber to the mixed hollow ball slurry in batches, stir while adding, and heat the slurry in a water bath. When one batch of fiber is completely dispersed in the slurry, add the next batch until the fiber is completely dispersed to form a hollow fiber ball slurry.
[0017] 6. Preparation of hollow fiber ball preform: Install the filtration device in place, which consists of the body mold, filter screen and vacuum device from top to bottom. Pour the dispersed hollow fiber ball slurry into the body mold sprayed with release agent, open the vacuum device and maintain pressure for a period of time to ensure that most of the dispersant in the preform is removed. Remove the preform from the body mold and place it in a drying oven for drying.
[0018] 7. Preparation of fiber / aluminum-based porous composite materials by vacuum infiltration method: Place the dried fiber / hollow sphere preform into a vacuum infiltration mold, place the cut aluminum ingot on the filled preform, place the vacuum infiltration mold into a high-temperature resistance furnace, heat up to 700°C at 300°C / h and keep warm to complete the preheating of the preform and the melting of aluminum. The molten aluminum covers the preform to form a sealing layer, turn on the vacuum equipment, and turn off the vacuum equipment when the aluminum liquid penetrates into the gap inside the preform; the casting solidifies and cools in the mold, and the casting is demolded to obtain a fiber / aluminum-based porous composite material. Description of the drawings:
[0019] Figure 1 It is a preparation flow chart of the present invention;
[0020] Figure 2 is a metallographic picture of the sample prepared in Example 1; Specific implementation method:
[0021] The present invention is further described in detail below with reference to the accompanying drawings and specific examples, but the protection scope of the present invention is not limited to the described contents.
[0022] Example 1
[0023] 1. Sol precursor configuration:
[0024] Step 1: Add 143 ml of tetraethyl orthosilicate (TEOS) to 71.5 ml of ethanol and stir well to mix;
[0025] Step 2: Take 23 ml of deionized water and 71.5 ml of ethanol, and drop 8 ml of 1 mol / L hydrochloric acid into the mixture, and mix thoroughly.
[0026] Step 3: under constant temperature stirring, slowly add the mixture of water and hydrochloric acid to the mixture of ethyl orthosilicate and ethanol according to the ratio, heat and stir at 60° C. under closed conditions for 30 minutes to obtain the desired SiO2 sol.
[0027] 2. Fiber pretreatment: Fiber pretreatment is divided into three processes: degumming, roughening and sol-gel. First, soak the basalt fiber in acetone to remove the glue, then soak it in 50g / L NaOH solution to roughen the fiber surface, then rinse it with distilled water several times to remove the residual alkali solution and dry it. Finally, soak the basalt fiber in the sol, infiltrate it under ultrasound for 5 minutes, and after fully drying, heat it to 470℃ at 5℃ / min for sintering to obtain SiO2 coating on the fiber surface.
[0028] 3. Preparation of fiber dispersant: Under the conditions of stirring with an electric stirrer and heating in a water bath, slowly add 1.2 g of carboxymethyl cellulose (CMC), 0.5 g of polyvinyl alcohol (PVA) and 0.5 g of an antistatic agent into 1000 ml of deionized water to prepare a fiber dispersant.
[0029] 4. Preparation of hollow ball slurry: Weigh 100g of floating beads (150-600μm) using an electronic balance, add 300ml of fiber dispersant, and fully mix under the conditions of heating at 80℃ in an ultrasonic water bath and stirring to form a suspension for use.
[0030] 5. Preparation of hollow fiber ball slurry: Weigh 3g (3-6mm) basalt fiber with an electronic balance, add the fiber to the mixed hollow ball slurry in batches of 10%, 15%, 20%, 20%, 15%, 10% and 10%, stir while adding, and heat the slurry in a water bath at 80°C. When one batch of fibers is completely dispersed in the slurry, add the next batch until the fibers are completely dispersed to form a hollow fiber ball slurry.
[0031] 6. Preparation of hollow fiber ball preform: Install the filtration device in place, which consists of the body mold, filter screen and vacuum device from top to bottom. Pour the dispersed hollow fiber ball slurry into the body mold sprayed with release agent, turn on the vacuum device and maintain the pressure at a flow rate of 5L / min for 3-5 minutes to ensure that most of the dispersant in the preform is removed. Remove the preform from the body mold and place it in a drying oven for drying.
[0032] 7. Preparation of fiber / aluminum-based porous composite materials by vacuum infiltration method: Place the dried fiber / hollow sphere preform into a vacuum infiltration mold, place the cut aluminum ingot on the filled preform, place the vacuum infiltration mold into a high-temperature resistance furnace, heat up to 700°C at 300°C / h and keep warm to complete the preheating of the preform and the melting of aluminum. The molten aluminum covers the preform to form a sealing layer, turn on the vacuum equipment to draw a vacuum at a flow rate of 10L / min, and turn off the vacuum equipment when the aluminum liquid penetrates into the gap inside the preform; the casting solidifies and cools in the mold, and the casting is demolded to obtain a fiber / aluminum-based porous composite material.
[0033] Example 2
[0034] 1. Sol precursor configuration:
[0035] The process of preparing TiO2 sol is as follows:
[0036] 21.2 g of tetrabutyl titanate was poured into 36 g of anhydrous ethanol and stirred to make the mixed solution uniform. While stirring, 3.74 g of acetic acid was slowly dripped in, and then a mixed solution of 35.7 g of anhydrous ethanol and 3.4 g of distilled water was slowly added and stirred for about 3 hours to form a transparent homogeneous sol.
[0037] 2. Fiber pretreatment: Fiber pretreatment is divided into three steps: degumming, roughening and sol-gel. First, the alumina fiber is soaked in acetone to remove the glue, and then soaked in 30g / L NaOH solution to roughen the fiber surface. Then, it is rinsed with distilled water several times to remove the residual alkali solution and dried. Finally, the fiber is soaked in the sol, infiltrated under ultrasound for 5 minutes, and after being fully dried, the temperature is raised to 500℃ at 5℃ / min for sintering to obtain a TiO2 coating on the fiber surface.
[0038] 3. Preparation of fiber dispersant: Under the conditions of stirring with an electric stirrer and heating in a water bath, slowly add 2 g of carboxymethyl cellulose (CMC), 0.5 g of polyvinyl alcohol (PVA) and 0.5 g of an antistatic agent into 1000 ml of deionized water to prepare a fiber dispersant.
[0039] 4. Preparation of hollow ball slurry: Weigh 100g of hollow alumina balls (2000-3000μm) and 50g of hollow silicon carbide balls (1500-2000μm) using an electronic balance, add 300ml of fiber dispersant, and mix thoroughly under stirring and heating at 80°C in an ultrasonic water bath to form a suspension for use.
[0040] 5. Preparation of hollow fiber ball slurry: Weigh 5g (3-6mm) alumina fiber with an electronic balance, and add the fiber to the mixed hollow ball slurry in batches according to 15%, 15%, 15%, 20%, 15%, 10% and 10% by weight, stirring while adding, and the slurry is always heated in a water bath at 80°C. After one batch of fibers is completely dispersed in the slurry, add the next batch until the fibers are completely dispersed to form a hollow fiber ball slurry.
[0041] 6. Preparation of hollow fiber ball preform: Install the filtration device in place, which consists of the body mold, filter screen and vacuum device from top to bottom. Pour the dispersed hollow fiber ball slurry into the body mold sprayed with release agent, turn on the vacuum device and maintain the pressure at a flow rate of 5L / min for 3-5 minutes to ensure that most of the dispersant in the preform is removed. Remove the preform from the body mold and place it in a drying oven for drying.
[0042] 7. Preparation of fiber / aluminum-based porous composite materials by vacuum infiltration method: Place the dried fiber / hollow sphere preform into a vacuum infiltration mold, place the cut aluminum ingot on the filled preform, place the vacuum infiltration mold into a high-temperature resistance furnace, heat it to 700°C at 300°C / h and keep it warm to complete the preheating of the preform and the melting of the aluminum. The molten aluminum covers the preform to form a sealing layer, turn on the vacuum equipment and draw a vacuum at a flow rate of 10L / min. When the system pressure reaches -0.4 to -0.9MPa, the aluminum liquid penetrates into the gap inside the preform and then the vacuum equipment is turned off; the casting solidifies and cools in the mold, and the casting is demolded to obtain a fiber / aluminum-based porous composite material.
[0043] Example 3
[0044] 1. Sol precursor configuration:
[0045] a. The process of preparing SiO2 sol is as follows:
[0046] Step 1: Add 143 ml of tetraethyl orthosilicate (TEOS) to 71.5 ml of ethanol and stir well to mix;
[0047] Step 2: Take 23 ml of deionized water and 71.5 ml of ethanol, and drop 8 ml of 1 mol / L hydrochloric acid into the mixture, and mix thoroughly.
[0048] Step 3: under constant temperature stirring, slowly add the mixture of water and hydrochloric acid to the mixture of ethyl orthosilicate and ethanol according to the ratio, heat and stir at 60° C. under closed conditions for 30 minutes to obtain the desired SiO2 sol.
[0049] b. The process of preparing TiO2 sol is as follows:
[0050] 21.2 g of tetrabutyl titanate was poured into 36 g of anhydrous ethanol and stirred to make the mixed solution uniform. While stirring, 3.74 g of acetic acid was slowly dripped in, and then a mixed solution of 35.7 g of anhydrous ethanol and 3.4 g of distilled water was slowly added and stirred for about 3 hours to form a transparent homogeneous sol.
[0051] 2. Fiber pretreatment: First, soak the basalt and silicon carbide fibers in acetone to remove the glue, and then soak them in 50g / L and 30g / L NaOH solutions respectively to roughen the fiber surface, then rinse with distilled water several times to remove the residual alkali solution and dry. Finally, soak the basalt fiber in a sol, infiltrate it under ultrasound for 5 minutes, and sinter it at 5℃ / min to 470℃ after sufficient drying to obtain SiO2 coating on the fiber surface. Soak the silicon carbide fiber in b sol, infiltrate it under ultrasound for 5 minutes, and sinter it at 5℃ / min to 500℃ after sufficient drying to obtain TiO2 coating on the fiber surface.
[0052] 3. Preparation of fiber dispersant: Under the conditions of stirring with an electric stirrer and heating in a water bath, slowly add 1.2 g of carboxymethyl cellulose (CMC), 1 g of polyvinyl alcohol (PVA) and 1 g of antistatic agent into 1000 ml of deionized water to prepare a fiber dispersant.
[0053] 4. Preparation of hollow ball slurry: Weigh 50g of fly ash hollow balls (150-250μm) and 80g of glass microspheres (70-100μm) using an electronic balance, add 300ml of fiber dispersant, and mix thoroughly under ultrasonic water bath heating at 80°C and stirring to form a suspension for use.
[0054] 5. Preparation of hollow fiber ball slurry: Weigh 2g (6-9mm) basalt fiber and 2g (1mm) silicon carbide fiber with an electronic balance, and add basalt fiber and alumina fiber to the mixed hollow ball slurry in batches according to 10%, 20%, 20%, 15%, 15%, 10% and 10% respectively, stirring while adding, and the slurry is always heated in a water bath at 80°C. After one batch of fibers is completely dispersed in the slurry, add the next batch until the fibers are completely dispersed to form a hollow fiber ball slurry.
[0055] 6. Preparation of hollow fiber ball preform: Install the filtration device in place, which consists of the body mold, filter screen and vacuum device from top to bottom. Pour the dispersed hollow fiber ball slurry into the body mold sprayed with release agent, turn on the vacuum device and maintain the pressure at a flow rate of 5L / min for 3-5 minutes to ensure that most of the dispersant in the preform is removed. Remove the preform from the body mold and place it in a drying oven for drying.
[0056] 7. Preparation of fiber / aluminum-based porous composite materials by vacuum infiltration method: Place the dried fiber / hollow sphere preform into a vacuum infiltration mold, place the cut aluminum ingot on the filled preform, place the vacuum infiltration mold into a high-temperature resistance furnace, heat up to 700°C at 300°C / h and keep warm to complete the preheating of the preform and the melting of aluminum. The molten aluminum covers the preform to form a sealing layer, turn on the vacuum equipment to draw a vacuum at a flow rate of 10L / min, and turn off the vacuum equipment when the aluminum liquid penetrates into the gap inside the preform; the casting solidifies and cools in the mold, and the casting is demolded to obtain a fiber / aluminum-based porous composite material.
[0057] Example 4
[0058] 2. Fiber pretreatment: First, soak the glass fiber and nickel-plated carbon fiber in acetone to remove the glue, then rinse them with distilled water several times to remove the residual acetone and dry them.
[0059] 3. Preparation of fiber dispersant: Under the conditions of stirring with an electric stirrer and heating in a water bath, slowly add 2.4 g of carboxymethyl cellulose (CMC), 1.2 g of polyvinyl alcohol (PVA) and 1.2 g of antistatic agent into 1000 ml of deionized water to prepare a fiber dispersant.
[0060] 4. Preparation of hollow ball slurry: Weigh 100g of fly ash hollow balls with an electronic balance, add 300ml of fiber dispersant, and fully mix under the conditions of heating at 80°C in an ultrasonic water bath and stirring to form a suspension for use.
[0061] 5. Preparation of hollow fiber ball slurry: Use an electronic balance to weigh 2g (3mm) glass fiber and 2g (3-6mm) nickel-plated carbon fiber, and add basalt fiber and nickel-plated carbon fiber to the mixed hollow ball slurry in batches of 10%, 20%, 20%, 15%, 15%, 10% and 10% respectively, stirring while adding, and the slurry is always heated in a water bath at 80°C. After one batch of fibers is completely dispersed in the slurry, add the next batch until the fibers are completely dispersed to form a hollow fiber ball slurry.
[0062] 6. Preparation of hollow fiber ball preform: Install the filtration device in place, which consists of the body mold, filter screen and vacuum device from top to bottom. Pour the dispersed hollow fiber ball slurry into the body mold sprayed with release agent, turn on the vacuum device and maintain the pressure at a flow rate of 5L / min for 3-5 minutes to ensure that most of the dispersant in the preform is removed. Remove the preform from the body mold and place it in a drying oven for drying.
[0063] 7. Preparation of fiber / aluminum-based porous composite materials by vacuum infiltration method: Place the dried fiber / hollow sphere preform into a vacuum infiltration mold, place the cut aluminum ingot on the filled preform, place the vacuum infiltration mold into a high-temperature resistance furnace, heat up to 700°C at 300°C / h and keep warm to complete the preheating of the preform and the melting of aluminum. The molten aluminum covers the preform to form a sealing layer, turn on the vacuum equipment to draw a vacuum at a flow rate of 10L / min, and turn off the vacuum equipment when the aluminum liquid penetrates into the gap inside the preform; the casting solidifies and cools in the mold, and the casting is demolded to obtain a fiber / aluminum-based porous composite material.
Claims
1. A method for preparing a fiber-reinforced aluminum-based porous composite material, characterized in that: The following steps are involved: Step 1: Fiber pretreatment: The fiber is debonded, the fiber surface is roughened, and finally the fiber is immersed in the sol. After drying, the fiber is sintered to obtain the coated fiber. Step 2: Prepare hollow ball slurry: The raw materials in the dispersant are added into deionized water according to a certain proportion and heated and stirred to obtain the dispersant after being completely dissolved. The hollow balls are added into the dispersant according to a certain proportion and fully mixed under the conditions of ultrasonic water bath heating and stirring to form a suspension. Step 3: Preform preparation: The fibers obtained in step 1 are added in batches to the hollow ball slurry obtained in step 2, and stirred while adding. The slurry is always heated in a water bath until the fibers are completely dispersed to form a fiber hollow ball slurry. The slurry is poured into a suction filtration device for spraying a release agent to remove the dispersant in the slurry, and then the preform is removed from the device and placed in a drying oven for drying to obtain a preform. Step 4: Preparation of fiber / aluminum-based porous composite material: The preform obtained in step 3 is made into a fiber / aluminum-based porous composite material using a vacuum infiltration method.
2. The method for preparing the fiber-reinforced aluminum-based porous composite material according to claim 1, characterized in that: The fiber in step 1 is basalt fiber, alumina fiber, glass fiber, carbon fiber and silicon carbide fiber; the fiber length ranges from 1 to 9 mm.
3. The method for preparing the fiber-reinforced aluminum-based porous composite material according to claim 1, characterized in that: The raw materials of the dispersant in step 2 are carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and antistatic agent; the concentration range of the components is 0.8:0.5:0.5–2.4:1.2:1.2 g / L.
4. The method for preparing the fiber-reinforced aluminum-based porous composite material according to claim 1, characterized in that: The hollow balls in step 2 are floating beads, hollow alumina balls, hollow microballs and hollow silicon carbide balls; their particle sizes range from 70 to 3000 μm; and the added volume of the hollow balls accounts for 0-81% of the volume of the dispersant.
5. The method for preparing the fiber-reinforced aluminum-based porous composite material according to claim 1, characterized in that: The amount of the fiber used in step 3 is in the range of 0.001-0.013 of the stacking volume of the hollow spheres; The number of times of adding the fiber multiple times ranges from 5 to 10 times; the amount of fiber added each time does not exceed 20% of the total fiber added mass.
6. The method for preparing a fiber-reinforced aluminum-based porous composite material according to claim 1, characterized in that: The filtration device in step 3 includes, from top to bottom, a blank mold, a filter screen and a vacuum device; the temperature of the preform drying process does not exceed 90°C.
7. The method for preparing a fiber-reinforced aluminum-based porous composite material according to claim 1, characterized in that: In the vacuum infiltration process of step 4, the preform is preheated at a temperature of 650-680° C. for a preheating time of 1.5-6 hours.
8. The method for preparing a fiber-reinforced aluminum-based porous composite material according to claim 1, characterized in that: The stirring speed ranges from 100 to 500 r / min during the dispersion process; the heating in the dispersion process is performed in a water bath with a heating temperature range of 60 to 100°C.
Citation Information
Patent Citations
Alumina-fiber-enhanced hydroxyapatite ceramic-based composite material and preparation method thereof
CN104909742A
Sandwich structure composite and preparation method thereof
CN110230013A
Metal-based composite material and preparation method thereof
CN111074178A
Preparation method of chopped carbon fiber reinforced magnesium-based composite material
CN111155038A
Preparation method of density gradient hollow sphere reinforced aluminum-based porous composite material
CN114231778A